Nutritional and phytochemical content of Swiss chard from Montenegro, under different fertilization and irrigation treatments. Issue 2 (4th February 2019) - Ivanović, Ljubica; Milašević, Ivana; Topalović, Ana; Ðurović, Dijana; Mugoša, Boban; Knežević, Mirko; Vrvić, Miroslav
Abstract : Purpose: The purpose of this paper is to evaluate both nutrient and phytochemical content of Swiss chard grown under different fertilization and irrigation treatments and the effect of these treatments on the tested parameters. Design/methodology/approach: Samples of fresh Swiss chard were collected from the experimental field of Ljeskopolje, Montenegro, where chard was grown under different fertilization and irrigation treatments. Swiss chard samples were analyzed for nutritional and antioxidant parameters. Findings: In this study, the authors found that 100 g of Swiss chard is a good source of total chlorophyll (47.13 mg), carotenoids (9.85 mg), minerals as well as vitamin C (26.88 mg) expressed as mean values. Total phenol and flavonoid compounds content were (138.59  µ g gallic acid equivalent (GAE) and 11.91  µ g catechin equivalent (CAE) per mg of water extract, respectively), also expressed as mean values. The total antioxidant capacity (IC50 values) determined by 1, 1-diphenyl-2-picrylhydrazyl assay ranged from 2.93 to 4.44 mg/mL of aquatic water extract. Different fertilization regimes affected the following parameters: phosphorous, protein content, chlorophyll a, chlorophyll b and vitamin C ( p <0.05), while different irrigation regimes did not have any effect on the tested parameters ( p >0.05), while interaction effect between fertilization and irrigation was found only for sodium and copper ( p <0.05). Originality/value: Swiss chard produced in Montenegro on a sandy clay loam soil with acid reaction contains appreciable amount of minerals, crude fibers, vitamin C, chlorophylls, carotenoids and polyphenols. The nutrient and phytochemical content of chard is equal or superior to other green leafy vegetables which are considered as functional food. It was identified as a potentially rich source of essential nutrients and phytochemical compounds. The promotion of higher consumption and production of Swiss chard may represent a natural and sustainable alternative for improving human health.